Prenatal vitamin A supplementation associated with adverse child behavior at 3 years in a prospective birth cohort in Japan. Issue 9 (21st June 2016) - Ishikawa, Yohei; Tanaka, Haruka; Akutsu, Taisuke; Koide, Kentaro; Sakuma, Mio; Okazaki, Minoru; Ida, Hiroyuki; Urashima, Mitsuyoshi
Abstract: Background: Many pregnant women take vitamin supplements during pregnancy. The aim of this paper was to clarify the effects of dietary supplementation prior to and/or during pregnancy on child behavior. Methods: A prospective birth cohort study from pregnancy to 3 years of age involving 1271 pairs of Japanese pregnant women and their newborns, was carried out. The women completed a self‐administered questionnaire during the third trimester of pregnancy. To evaluate deviations in child behavior as an endpoint, each mother completed the Japanese Child Behavior Checklist for ages 2–3 years after 3 years of birth. Participant characteristics were compared between supplement takers and non‐takers. Results: Among many kinds of supplements, intake of supplemental vitamin A/β‐carotene prior to and/or during pregnancy was associated with hazardous effects on child behavior at 3 years of age (total t ‐score, P = 0.003; internal t ‐score, P = 0.027; external t ‐score, P = 0.013). This association held true even after adjusting for age, number of deliveries, infertility treatment, consumption of fast food, smoking status, maternal and paternal education, maternal and paternal income, gestational age at birth, anthropometry at birth (weight, height, head circumference and body circumference), and the State–Trait Anxiety Inventory at 3 years of age by means of multiple imputation. Conclusions: Intake of supplemental vitamin A prior to and/or during pregnancy may worsen child behavior at 3 years of age.